Metabolismo energético, sistema antioxidante e atividade de colinesterases de ovos e larvas de rhamdia quelen: desenvolvimento em aguas de rios com diferenças de uso e ocupação de solo - Oliveira, Camila Maria Toigo de (2020)
The diversity in land use and occupation also results in different interconnected effects on the environments, many of them negative. As an example, we have the continuous use of land for agriculture in which the massive use of pesticides dispenses large quantities of chemical compounds in water through leaching. The presence of these compounds in the water causes adverse reactions in the organisms. These effects can be measured by enzymatic quantification of enzymes in the energy metabolism and antioxidant system, measurement of the lipoperoxidation reaction and cholinesterase activity. Therefore, native species with economic potential are well accepted for such studies. In our case, a native species Rhamdia quelen was used for the testing of environmental biomarkers. The waters of streams in the western region of Paraná were used, being collected from the waters of a stream considered impacted (Rio Tormenta) and another stream considered preserved because it is located within the Iguaçu National Park (Rio Manoel Gomes). R. quelen oocytes were fertilized with water and followed for 12h, 24h, 48h and 72h in development. In these times of experimentation, a pool of organisms was sampled, properly packed for further analysis of energy metabolism, antioxidant system, oxidative stress and cholinesterase enzyme activity. Animals developed in river water reference the induction of aerobic metabolism in the first 24 hours of development and a drastic reduction between 48 and 72 hours. In the same period, lipoperoxide production and modulation of the antioxidant defense system were observed. Changes in the enzymatic activities of energy metabolism (HK, PFK, LDH, CS, MDH) and of x the antioxidant defense system (CAT, GPX, GR, GST) were found in animals developed with water from the river considered impacted in relation to the reference river. In addition, the characteristics of contamination by anticholinesterase compounds such as organophosphates and carbamates, such as the inhibition of cholinesterase enzymes. The effects caused by pesticides present in trace gifts in stream waters can be diverse. Sites with constant compound use can trigger deleterious effects of organisms in early stages of development and alter metabolic enzyme activities and defense of the organism.